Bearing bush large-thickness coating preparation method based on radio frequency magnetron sputtering process
Through the RF magnetron sputtering process and the alternating deposition method of composite aluminum-tin copper alloy targets, the problem of difficulty in preparing large-thick bearing slab coatings in the existing PVD magnetron sputtering process is solved, and high-quality and high-bound force bearing slab coating preparation is achieved, which improves the performance and service life of bearing slabs.
Patent Information
- Application Number
- CN202510080370.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-18
AI Technical Summary
The existing PVD magnetron sputtering process is difficult to effectively prepare large-thick bearing coatings, and there are often problems of many coating defects and poor bonding forces, which affect the overall performance and service life of bearing coatings.
Using the RF magnetron sputtering process, a large-thickness coating with bearing shells that adapt to high velocity, high load and high fatigue resistance are prepared by pretreatment of bearing shells, preparation of composite aluminum-tin copper alloy targets and alternating deposition of tin and aluminum-rich plating layers.
The high-quality preparation of bearing shell plating is achieved, with smooth surface, uniform cross-sectional morphology, low porosity, high density, and a binding force of above 4B, extending the service life of bearing shells.
Smart Images

Figure CN119843234A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of bearing bush coating preparation, and in particular relates to a method for preparing a bearing bush coating with a large thickness based on a radio frequency magnetron sputtering process. Background Art
[0002] In today's situation of rapid development of industrial technology, mechanical equipment plays a vital role in many fields. As a key component, bearings are the "joints" of mechanical equipment, and they undertake key missions such as supporting the journal, reducing friction, and transmitting loads. Their performance plays a decisive role in the reliability and service life of the entire equipment. In terms of improving the performance of bearings, the preparation of bearing surface coatings has become a highly-anticipated research direction. By preparing a coating on the surface of the bearing, it can better cope with a variety of complex working environments, significantly enhance wear resistance, corrosion resistance and other properties, and thus ensure the stable operation of the equipment.
[0003] Traditional coating production processes mostly rely on ternary electroplating technology. However, as my country pays more and more attention to environmental protection, the environmental protection department has put forward higher standards for the discharge and treatment of electroplating waste liquid. This requires companies to invest a lot of money in waste liquid treatment and related environmental protection facilities in the process of complying with environmental protection regulations, resulting in rising production costs and an urgent need to update the bearing coating process.
[0004] At present, PVD bearings, as the fourth-generation bearing products with the most advanced manufacturing technology in the world, have demonstrated higher load capacity and high wear resistance with the help of magnetron sputtering technology (PVD), and are an inevitable trend for the future development of engine bearings in my country. However, there are still many shortcomings in the actual use of PVD magnetron sputtering technology to prepare bearing coatings. Patent CN112111717A discloses a bearing composite coating processing method and a bearing composite coating based on PVD technology, and patent CN106319476A discloses a treatment method for improving the bonding strength of bearing coatings. It is mentioned that the PVD process often has many coating defects and poor bonding strength, and it is difficult to effectively prepare thick coatings. This not only affects the overall performance of the bearing, but also shortens its service life, limiting its application in some high-end equipment that has higher requirements for bearings.
[0005] It can be seen that the development of a method for preparing thick bearing coatings based on radio frequency magnetron sputtering technology is of great practical significance. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention proposes a method for preparing a thick coating on a bearing with a gradient composition, and utilizes radio frequency magnetron sputtering technology to prepare a thick tin-aluminum-copper alloy coating on the working surface of the bearing, so that it has the characteristics of adapting to high speed, high load and high fatigue resistance.
[0007] A method for preparing a thick coating on a bearing bush based on a radio frequency magnetron sputtering process, specifically comprising the following steps:
[0008] (1) Bearing pretreatment: Treat the surface of the bearing base to remove grease and impurities on the surface to obtain the treated bearing base;
[0009] (2) preparing an aluminum-tin-copper alloy melt: adding metal raw materials for smelting under a vacuum environment to obtain an aluminum-rich aluminum-tin-copper alloy melt and a tin-rich aluminum-tin-copper alloy melt;
[0010] (3) Preparation of composite aluminum-tin-copper alloy target:
[0011] Alternately casting an aluminum-rich aluminum-tin-copper alloy melt and a tin-rich aluminum-tin-copper alloy melt to obtain a composite aluminum-tin-copper alloy target material with a multi-layer alternating structure, wherein the top layer of the target material is a tin-rich alloy layer;
[0012] (4) PVD magnetron sputtering:
[0013] The bearing substrate obtained in step (1) is sputtered and cleaned by using a radio frequency alternating current power supply. After the cleaned bearing substrate is preheated, it is sputtered by a molybdenum target to obtain a molybdenum interlayer; the molybdenum interlayer is surface activated, and then it is sputtered by a composite aluminum-tin-copper alloy target to alternately deposit tin-rich coatings and aluminum-rich coatings on the molybdenum interlayer to obtain a magnetron sputtering bearing thick coating.
[0014] in:
[0015] In the step (1), the surface of the bearing base is treated by: treating the surface of the bearing base with an ammonium persulfate solution, placing the bearing base in an aminosulfonic acid electrolyte for anodizing, and then cleaning the bearing base with ultrasonic oscillation to obtain the treated bearing base;
[0016] The mass concentration of the ammonium persulfate solution is 10% to 30%, the surface treatment time is 10min to 30min, and the temperature is 40°C to 60°C; the mass concentration of the aminosulfonic acid electrolyte is 10% to 30%, the oxidation time is 20min to 40min, and the temperature is 50°C to 70°C.
[0017] In the step (2), the vacuum degree of the environment is ≥ 1×10 -6 Pa; the raw materials used to prepare the aluminum-rich aluminum-tin-copper alloy are calculated by mass fraction as follows: Sn: 22%-25%, Cu: 0.3%-0.5%, and the balance is Al; the raw materials used to prepare the tin-rich aluminum-tin-copper alloy are calculated by mass fraction as follows: Al: 35%-38%, Cu: 0.3%-0.5%, and the balance is Sn; the vacuum melting temperature is controlled at 750°C-900°C, and the melting time is 0.5h-1h.
[0018] In the step (3), the preparation process of the composite aluminum-tin-copper alloy target is specifically as follows: by pressure casting, an aluminum-rich aluminum-tin-copper alloy melt is injected into a mold to form an aluminum-rich alloy layer on the target copper substrate, and then a tin-rich aluminum-tin-copper alloy melt is covered on the aluminum-rich alloy layer in the same manner to form a tin-rich alloy layer, and the casting operation is performed alternately to obtain a composite aluminum-tin-copper alloy target with a multi-layer alternating structure;
[0019] The specific injection method of the aluminum-rich aluminum-tin-copper alloy melt is as follows: the pre-smelted aluminum-rich aluminum-tin-copper alloy melt is maintained at 650° C. to 750° C., a pressure casting device is started with an initial casting pressure of 0.5 MPa to 1.0 MPa, and the melt is slowly flowed through the casting pipe to the mold inlet at the copper substrate, and the injection speed of the melt is controlled, and the initial injection speed is 0.0001 m / s. 3 / s~0.0003m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00005m 3 / s~0.00008m 3 / s, so that the melt continues to slowly fill to the target thickness to form an aluminum-rich alloy layer;
[0020] The target thickness of each aluminum-rich alloy layer and tin-rich alloy layer is 2μm to 4μm, and the thickness of the composite aluminum-tin-copper alloy target is 20μm to 28μm. After each alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt of this layer is completely solidified and tightly combined with the lower alloy layer, the next step is carried out.
[0021] In the step (4), the process of sputtering and cleaning the bearing substrate is specifically as follows: placing the bearing substrate, the molybdenum target material, and the composite aluminum-tin-copper alloy target material in a sputtering chamber respectively, evacuating the chamber to a vacuum, and slowly introducing argon gas to adjust the pressure; turning on the radio frequency AC power supply, starting the self-made target baffle, isolating the target material and the bearing substrate from each other, using argon gas as the sputtering gas, controlling the radio frequency frequency to ionize the argon gas, and using the ionized argon gas ions to bombard the bearing substrate to improve the cleanliness of the microstructure of the bearing substrate;
[0022] The sample chamber is evacuated to a vacuum degree of ≥1×10 -4 Pa, introduce argon gas to adjust the sputtering pressure to 0.6Pa~0.8Pa;
[0023] The parameters of the sputtering bearing bush substrate are: radio frequency of 13 MHz to 15 MHz, power of 700 W to 900 W, and duration of 5 min to 10 min.
[0024] In the step (4), after the bearing base is preheated, the target baffle is retracted, and the distance between the target and the bearing base is controlled to perform sputtering of the molybdenum interlayer; the preheating temperature of the bearing base is 100°C to 150°C, and the distance between the target and the bearing base is 30mm to 50mm.
[0025] In the step (4), the process parameters of the molybdenum target sputtering the bearing substrate are specifically as follows: the RF frequency is 10MHz~12MHz, the power is 500W~700W, the substrate bias is -50V~-70V, the sputtering gas pressure is 6Pa~9Pa, and the sputtering time is 0.5h~1h; during the sputtering process, the temperature on the back of the target material is kept below 150°C.
[0026] In the step (4), the surface activation process of the bearing bush molybdenum interlayer is specifically as follows: start the target baffle, bombard the molybdenum interlayer with ionized argon ions, the radio frequency frequency is 10MHz to 12MHz, the power is 500W to 700W, and the duration is 3min to 5min.
[0027] In the step (4), the process of sputtering the composite aluminum-tin-copper alloy target material is specifically as follows: retracting the target baffle, bombarding the composite aluminum-tin-copper alloy target material with ionized argon gas particles, and depositing a tin-rich coating and an aluminum-rich coating with alternating compositions on the molybdenum interlayer of the bearing shell substrate, first obtaining a tin-rich aluminum-tin-copper alloy deposition, then obtaining an aluminum-rich aluminum-tin-copper alloy deposition, and then depositing in sequence until all the target materials are sputtered, thereby obtaining a bearing shell coating whose outermost coating layer is an aluminum-rich aluminum-tin-copper alloy;
[0028] The process parameters of the sputtering composite aluminum-tin-copper alloy target are: RF frequency of 10MHz to 12MHz, power of 600W to 800W, substrate bias of -50V to -70V, sputtering gas pressure of 6Pa to 9Pa, and sputtering time of 10h to 14h; during the sputtering process, the temperature on the back of the target is kept below 100°C; the thickness of the obtained bearing coating is 20μm to 28μm.
[0029] In the step (4), the target baffle material used in the PVD magnetron sputtering process is 45# steel.
[0030] In the step (4), the adhesion of the thick coating of the magnetron sputtering bearing bush is tested by the cross-grid method, and the coating bonding strength reaches 4B level or above; after the 180° bending test, the coating does not peel off.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The method for preparing thick bearing coatings based on radio frequency magnetron sputtering technology of the present invention, in the bearing pretreatment process, the persulfate ions have strong oxidizing properties, and undergo oxidation reactions with reducing substances such as organic matter and oil stains on the surface of parts and components, decomposing them into smaller substances that are more soluble in water; during the anodic oxidation process of aminosulfonic acid, the acidic aminosulfonic acid electrolyte undergoes an acid-base neutralization reaction with alkaline substances, metal oxides, etc. on the surface of parts and components, converting these impurities into water-soluble salts; through the above-mentioned pretreatment process, grease and impurities on the bearing surface are effectively removed, and the adhesion of the coating is improved.
[0033] 2. The present invention adopts a radio frequency alternating current process, which can produce a higher density and more stable plasma. The radio frequency electric field can continuously excite and maintain the ionization of the gas, so that the number of ions and electrons in the plasma is larger and the energy distribution is more uniform, which helps to improve the sputtering rate and coating efficiency, and the deposited coating is more uniform and dense in microstructure, and has better physical and chemical properties. Therefore, the use of the radio frequency alternating current process can more evenly sputter the target material composed of multiple elements, so that the composition of the deposited coating is closer to the original composition of the target material, ensuring the quality and performance of the coating.
[0034] 3. The vacuum melting composite aluminum-tin-copper alloy target material used in the present invention has a precise control of the composition ratio, which provides a guarantee for the preparation of high-performance coatings.
[0035] 4. The present invention adopts a single composite aluminum-tin-copper alloy target. In terms of equipment, only one target needs to be installed in the magnetron sputtering equipment. Compared with the use of two targets for alternating sputtering, which requires the configuration of two independent target installation positions, corresponding power supplies and control circuits and other complex equipment structures, a single target can significantly simplify the equipment structure. This not only reduces the manufacturing cost of the equipment and reduces the overall volume of the equipment, but also makes it easier to maintain the equipment, reduces the probability of failures due to multiple target-related components, and improves the stability and reliability of the equipment operation. In terms of operation, the use of a single composite target does not require frequent switching of different targets, avoiding the need to accurately control the target switching time and adjust the sputtering parameters (such as power, air pressure, etc.) corresponding to different targets when two targets are alternately sputtered. Complex operation links. The operator only needs to set the sputtering parameters for a single composite target to stably perform sputtering coating work, which greatly reduces the difficulty of operation and improves production efficiency. Especially for continuous production processes with high automation requirements, it is easier to achieve stable and efficient automated operations.
[0036] 5. The target material components of the present invention are tin-rich aluminum-tin-copper alloy layer and aluminum-rich aluminum-tin-copper alloy layer, which are pre-alternated. During the sputtering process, since the layers are closely adjacent, the sputtered atoms can be more evenly mixed in the process of flying to the substrate for deposition, thereby making the distribution of the coating composition formed on the substrate more uniform.
[0037] 6. In the coating prepared by the present invention, during the sputtering process, the atoms of the adjacent aluminum-rich layer and tin-rich layer will diffuse to form an atomic interlocking microstructure. The atoms in the aluminum-rich layer will penetrate into the tin-rich layer, and vice versa, thereby producing a "riveting"-like effect between the two layers, increasing the "contact points" and "anchor points" that are interconnected between different regions inside the coating, and strengthening the bonding between the layers and between the coating and the substrate. This atomic-level interaction makes the bonding of the alternating composite coatings tighter, which is far better than the simple adhesion of the single-component coating to the substrate, and effectively improves the bonding strength. The aluminum-rich aluminum-tin-copper alloy is usually relatively hard, and can provide better support and deformation resistance in the outermost layer of the coating; while the tin-rich aluminum-tin-copper alloy has better toughness and can buffer external forces and absorb energy by appropriate deformation when subjected to force. The coating formed by the alternating composite of the two, when facing external forces, the synergistic combination of hardness and toughness can better adapt to complex stress environments, reduce the risk of the coating detaching from the substrate, and improve the overall bonding strength. Alternating composite sputtering affects the grain growth of the coating, thereby achieving grain refinement. The refined grain structure contains more grain boundaries, which can hinder dislocation movement and disperse stress. When there is an external force that destroys the bonding between the coating and the substrate, the numerous grain boundaries can effectively delay the generation and expansion of cracks and enhance the bonding strength of the coating. Composite coatings often form a special texture due to the alternating deposition of two alloys, that is, the preferred orientation arrangement of crystals in space. This texture is conducive to the formation of a tighter chemical bond or physical adsorption between the coating and the substrate atoms in the direction perpendicular to the substrate surface, strengthening the bonding between the coating and the substrate.
[0038] 7. The present invention optimizes the process parameters and methods of PVD magnetron sputtering during the preparation process, successfully prepares a bearing coating with large thickness, uniform morphology and strong bonding force, and solves the problems existing in the existing magnetron sputtering process of preparing large thickness coatings.
[0039] 8. The coating prepared by the method provided by the present invention has excellent performance, ensures the quality and reliability of the coating, and provides a new solution and technical support for the preparation of thick and high-performance bearings. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The surface microstructure SEM morphology of the magnetron sputtering bearing coating prepared in Example 1 of the present invention;
[0041] Figure 2 SEM morphology of the cross-sectional microstructure of the magnetron sputtering bearing coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0042] Example 1
[0043] A method for preparing a thick coating on a bearing bush based on a radio frequency magnetron sputtering process, specifically comprising the following steps:
[0044] (1) Bearing pretreatment: The surface of the bearing substrate was treated with a 10% ammonium persulfate solution for 30 min at 60°C. The substrate was then anodized in a 10% aminosulfonic acid electrolyte for 40 min at 70°C. The treated bearing substrate was cleaned by ultrasonic oscillation.
[0045] (2) Preparation of aluminum-tin-copper alloy melt: The vacuum degree of the reaction chamber is 1×10 -6 Pa environment, aluminum, tin and copper metal raw materials are added according to their mass fractions for smelting, the smelting temperature is controlled at 750°C, the smelting time is 1 hour, and aluminum-rich aluminum-tin-copper alloy melt and tin-rich aluminum-tin-copper alloy melt are respectively obtained; wherein, the composition of the aluminum-rich aluminum-tin-copper alloy melt is Sn: 22%, Cu: 0.3%, and the balance is Al; the composition of the tin-rich aluminum-tin-copper alloy melt is Al: 35%, Cu: 0.3%, and the balance is Sn.
[0046] (3) Preparation of composite aluminum-tin-copper alloy target:
[0047] The pressure casting method is adopted. The pre-melted aluminum-rich aluminum-tin-copper alloy melt is kept at 690℃. The pressure casting device is turned on and started with an initial casting pressure of 1MPa. The melt is slowly flowed through the casting pipe to the mold inlet at the copper matrix. The injection speed of the melt is controlled. The initial injection speed is 0.0001m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00005m 3 / s, allowing the melt to continue to slowly fill to the target thickness, forming an aluminum-rich alloy layer with a thickness of 2μm on the target copper substrate.
[0048] After the aluminum-rich alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt of this layer is completely solidified and tightly combined with the lower alloy layer, the pre-melted tin-rich aluminum-tin-copper alloy melt is maintained at 660°C, and the pressure casting device is turned on with an initial casting pressure of 1MPa to allow the melt to slowly flow through the casting pipe to the mold inlet. The injection speed of the melt is controlled, and the initial injection speed is 0.0001m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00005m 3 / s, allowing the melt to continue to slowly fill to the target thickness, forming a tin-rich alloy layer with a thickness of 2μm.
[0049] After the tin-rich alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt layer is completely solidified and tightly combined with the lower alloy layer, the casting operation is performed alternately until the target thickness of 20μm is reached. The top layer of the target material is a tin-rich alloy layer, and a composite aluminum-tin-copper alloy target material with a multi-layer alternating structure is obtained.
[0050] (4) PVD magnetron sputtering:
[0051] The bearing base, molybdenum target, and composite aluminum-tin-copper alloy target were placed in the sputtering chamber respectively, and the chamber was evacuated to a vacuum degree of 1×10 -4 Pa, slowly introduce argon to adjust the sputtering pressure to 0.6Pa; turn on the RF AC power supply, start the 45# steel target baffle, isolate the target and the bearing substrate from each other, use argon as the sputtering gas, control the RF frequency to ionize the argon, and use the ionized argon ions to bombard the bearing substrate. The RF frequency is 13MHz, the power is 700W, and the duration is 5min to improve the cleanliness of the microstructure of the bearing substrate.
[0052] The treated bearing substrate is preheated to 100°C, the target baffle is retracted, the distance between the molybdenum target and the bearing substrate is controlled to be 30mm, and the sputtering process parameters are controlled for sputtering: RF frequency 10MHz, power 500W, substrate bias -50V, sputtering gas pressure 6Pa, sputtering time 0.5h, to obtain a molybdenum interlayer on the bearing substrate; during the sputtering process, the temperature on the back of the target is kept below 150°C.
[0053] The target baffle is started again, and the molybdenum interlayer is bombarded with ionized argon ions to activate its surface. The sputtering process parameters are: RF frequency of 10MHz, power of 500W, and duration of 3min. The target baffle is retracted again, and the composite aluminum-tin-copper alloy target is bombarded with ionized argon particles to deposit tin-rich coatings and aluminum-rich coatings with alternating compositions on the molybdenum interlayer of the bearing base. The sputtering process parameters are: RF frequency of 10MHz, power of 600W, substrate bias of -50V, sputtering pressure of 6Pa, and sputtering time of 10h; during the sputtering process, the temperature on the back of the target is kept below 100℃. First, a tin-rich aluminum-tin-copper alloy deposition is obtained on the molybdenum interlayer, and then an aluminum-rich aluminum-tin-copper alloy deposition is obtained. Subsequently, deposition is performed in sequence until all the targets are sputtered, and a bearing coating with an outermost coating of aluminum-rich aluminum-tin-copper alloy and a thickness of 20μm is obtained.
[0054] Scanning electron microscopy (SEM) was used to observe the surface and cross-sectional microstructure morphology of the bearing coating. Figure 1 The cross-sectional microstructure SEM morphology is shown in Figure 2As shown, the bearing coating prepared in this embodiment is smooth in surface, uniform in cross-sectional morphology, low in porosity and high in density compared with the coating of the same thickness prepared by the existing PVD technology. The adhesion of the bearing coating was tested by the cross-cutting test. The coating peeled off less than 5%, reaching the 4B grade. The coating had high bonding strength and was firmly bonded to the bearing substrate. After a 180° bending test, the coating did not peel off. The overall performance of the coating was good, providing reliable technical support for the application of thick-coated bearings.
[0055] Example 2
[0056] A method for preparing a thick bearing coating based on a radio frequency magnetron sputtering process specifically comprises the following steps:
[0057] (1) Bearing pretreatment: The surface of the bearing substrate was treated with an ammonium persulfate solution with a mass concentration of 20% for 20 minutes at a temperature of 50°C; it was then placed in an aminosulfonic acid electrolyte with a mass concentration of 20% for anodization for 30 minutes at a temperature of 60°C, and the treated bearing substrate was obtained by ultrasonic cleaning.
[0058] (2) Preparation of aluminum-tin-copper alloy melt: The vacuum degree of the reaction chamber is 1×10 -7 Pa environment, aluminum, tin and copper metal raw materials are added according to their mass fractions for smelting, the smelting temperature is controlled at 800°C, the smelting time is 1 hour, and aluminum-rich aluminum-tin-copper alloy melt and tin-rich aluminum-tin-copper alloy melt are respectively obtained; wherein, the composition of the aluminum-rich aluminum-tin-copper alloy melt is Sn: 23%, Cu: 0.4%, and the balance is Al; the composition of the tin-rich aluminum-tin-copper alloy melt is Al: 36%, Cu: 0.4%, and the balance is Sn.
[0059] (3) Preparation of composite aluminum-tin-copper alloy target:
[0060] The pressure casting method is adopted. The pre-melted aluminum-rich aluminum-tin-copper alloy melt is kept at 700℃. The pressure casting device is turned on and started with an initial casting pressure of 0.8MPa. The melt is slowly flowed through the casting pipe to the mold inlet at the copper matrix. The injection speed of the melt is controlled. The initial injection speed is 0.0001m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00005m 3 / s, allowing the melt to continue to slowly fill to the target thickness, forming an aluminum-rich alloy layer with a thickness of 2μm on the target copper substrate.
[0061] After the aluminum-rich alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt of this layer is completely solidified and tightly combined with the lower alloy layer, the pre-melted tin-rich aluminum-tin-copper alloy melt is maintained at 650°C, and the pressure casting device is turned on with an initial casting pressure of 0.8MPa. The melt is slowly allowed to flow through the casting pipe to the mold inlet, and the injection speed of the melt is controlled. The initial injection speed is 0.0001m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00005m 3 / s, allowing the melt to continue to slowly fill to the target thickness, forming a tin-rich alloy layer with a thickness of 2μm.
[0062] After the tin-rich alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt layer is completely solidified and tightly combined with the lower alloy layer, the casting operation is performed alternately until the target thickness of 24μm is reached. The top layer of the target material is a tin-rich alloy layer, and a composite aluminum-tin-copper alloy target material with a multi-layer alternating structure is obtained.
[0063] (4) PVD magnetron sputtering:
[0064] The bearing base, molybdenum target, and composite aluminum-tin-copper alloy target were placed in the sputtering chamber respectively, and the chamber was evacuated to a vacuum degree of 1×10 -5 Pa, slowly introduce argon to adjust the sputtering pressure to 0.7Pa; turn on the RF AC power supply, start the 45# steel target baffle, isolate the target and the bearing substrate from each other, use argon as the sputtering gas, control the RF frequency to ionize the argon, and use the ionized argon ions to bombard the bearing substrate. The RF frequency is 14MHz, the power is 800W, and the duration is 8min to improve the cleanliness of the microstructure of the bearing substrate.
[0065] The treated bearing base is preheated to 120°C, the target baffle is retracted, the distance between the molybdenum target and the bearing base is controlled to be 40mm, and the sputtering process parameters are controlled for sputtering: RF frequency 11MHz, power 600W, substrate bias -60V, sputtering gas pressure 8Pa, sputtering time 0.6h, and a molybdenum interlayer is obtained on the bearing base; during the sputtering process, the temperature on the back of the target is kept below 150°C. The molybdenum interlayer has a dense crystal structure and can effectively block the diffusion of elements such as tin. Moreover, the molybdenum interlayer can enhance the connection stability between the layers, thereby helping to improve the fatigue strength and load-bearing capacity of the bearing as a whole.
[0066] The target baffle is started again, and the molybdenum interlayer is bombarded with ionized argon ions to activate its surface. The sputtering process parameters are: RF frequency of 11MHz, power of 600W, and duration of 4min. Activating the surface of the molybdenum interlayer can increase the surface energy and generate more active sites, which is convenient for the subsequent deposition of atoms to attach.
[0067] The target baffle was retracted again, and the composite aluminum-tin-copper alloy target was bombarded with ionized argon particles to deposit tin-rich coatings and aluminum-rich coatings with alternating compositions on the molybdenum interlayer of the bearing base. The sputtering process parameters were: RF frequency of 11MHz, power of 700W, substrate bias of -60V, sputtering pressure of 8Pa, and sputtering time of 12h. During the sputtering process, the temperature on the back of the target was kept below 100°C. First, a tin-rich aluminum-tin-copper alloy deposition was obtained on the molybdenum interlayer, and then an aluminum-rich aluminum-tin-copper alloy deposition was obtained. Subsequently, deposition was carried out in sequence until all the targets were sputtered, and a bearing coating with an outermost coating of aluminum-rich aluminum-tin-copper alloy and a thickness of 24μm was obtained.
[0068] The bearing bush coating prepared in this embodiment has a smooth surface, uniform cross-sectional morphology, low porosity and high density. The adhesion of the bearing bush coating is tested by a cross-cut test, and the coating peeling is less than 5%, reaching the 4B grade. The coating has high bonding strength and is firmly bonded to the bearing bush substrate. After a 180° bending test, the coating has no peeling.
[0069] Example 3
[0070] A method for preparing a thick bearing coating based on a radio frequency magnetron sputtering process specifically comprises the following steps:
[0071] (1) Bearing pretreatment: The surface of the bearing substrate was treated with an ammonium persulfate solution with a mass concentration of 12% for 26 min at a temperature of 58°C. It was then placed in an aminosulfonic acid electrolyte with a mass concentration of 12% for anodization for 38 min at a temperature of 68°C. The treated bearing substrate was cleaned by ultrasonic oscillation.
[0072] (2) Preparation of aluminum-tin-copper alloy melt: The vacuum degree of the reaction chamber is 0.8×10 -6 Pa environment, aluminum, tin and copper metal raw materials are added according to their mass fractions for smelting, the smelting temperature is controlled at 770°C, the smelting time is 0.9h, and aluminum-rich aluminum-tin-copper alloy melt and tin-rich aluminum-tin-copper alloy melt are respectively obtained; wherein, the composition of the aluminum-rich aluminum-tin-copper alloy melt is Sn: 22%, Cu: 0.3%, and the balance is Al; the composition of the tin-rich aluminum-tin-copper alloy melt is Al: 35%, Cu: 0.3%, and the balance is Sn.
[0073] (3) Preparation of composite aluminum-tin-copper alloy target:
[0074] The pressure casting method is adopted. The pre-melted aluminum-rich aluminum-tin-copper alloy melt is maintained at 680°C. The pressure casting device is turned on and started with an initial casting pressure of 1MPa. The melt is slowly flowed through the casting pipe to the mold inlet at the copper matrix. The injection speed of the melt is controlled. The initial injection speed is 0.0002m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00006m 3 / s, allowing the melt to continue to slowly fill to the target thickness, forming an aluminum-rich alloy layer with a thickness of 2μm on the target copper substrate.
[0075] After the aluminum-rich alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt of this layer is completely solidified and tightly combined with the lower alloy layer, the pre-melted tin-rich aluminum-tin-copper alloy melt is maintained at 670°C, and the pressure casting device is turned on with an initial casting pressure of 1MPa to allow the melt to slowly flow through the casting pipe to the mold inlet. The injection speed of the melt is controlled, and the initial injection speed is 0.0002m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00006m 3 / s, allowing the melt to continue to slowly fill to the target thickness, forming a tin-rich alloy layer with a thickness of 2μm.
[0076] After the tin-rich alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt layer is completely solidified and tightly combined with the lower alloy layer, the casting operation is performed alternately until the target thickness of 20μm is reached. The top layer of the target material is a tin-rich alloy layer, and a composite aluminum-tin-copper alloy target material with a multi-layer alternating structure is obtained.
[0077] (4) PVD magnetron sputtering:
[0078] The bearing base, molybdenum target and composite aluminum-tin-copper alloy target were placed in the sputtering chamber respectively, and the chamber was evacuated to a vacuum degree of 0.8×10 -4 Pa, slowly introduce argon to adjust the sputtering pressure to 0.7Pa; turn on the RF AC power supply, start the 45# steel target baffle, isolate the target and the bearing substrate from each other, use argon as the sputtering gas, control the RF frequency to ionize the argon, and use the ionized argon ions to bombard the bearing substrate. The RF frequency is 13MHz, the power is 750W, and the duration is 6min to improve the cleanliness of the microstructure of the bearing substrate.
[0079] The treated bearing substrate was preheated to 110°C, the target baffle was retracted, the distance between the molybdenum target and the bearing substrate was controlled to be 32mm, and the sputtering process parameters were controlled for sputtering: RF frequency 10MHz, power 550W, substrate bias -55V, sputtering gas pressure 7Pa, sputtering time 0.6h, and a molybdenum interlayer was obtained on the bearing substrate; during the sputtering process, the temperature on the back of the target was kept below 150°C.
[0080] The target baffle is started again, and the molybdenum interlayer is bombarded with ionized argon ions to activate its surface. The sputtering process parameters are: RF frequency of 11MHz, power of 550W, and duration of 4min. The target baffle is retracted again, and the composite aluminum-tin-copper alloy target is bombarded with ionized argon particles to deposit tin-rich coatings and aluminum-rich coatings with alternating compositions on the molybdenum interlayer of the bearing base. The sputtering process parameters are: RF frequency of 11MHz, power of 650W, substrate bias of -55V, sputtering pressure of 7Pa, and sputtering time of 10h; during the sputtering process, the temperature on the back of the target is kept below 100℃. First, a tin-rich aluminum-tin-copper alloy deposition is obtained on the molybdenum interlayer, and then an aluminum-rich aluminum-tin-copper alloy deposition is obtained. Subsequently, deposition is carried out in sequence until all the targets are sputtered, and a bearing coating with an outermost coating of aluminum-rich aluminum-tin-copper alloy and a thickness of 20μm is obtained.
[0081] The bearing bush coating prepared in this embodiment has a smooth surface, uniform cross-sectional morphology, low porosity and high density. The adhesion of the bearing bush coating is tested by a cross-cut test, and the coating peeling is less than 5%, reaching the 4B grade. The coating has high bonding strength and is firmly bonded to the bearing bush substrate. After a 180° bending test, the coating has no peeling.
[0082] Example 4
[0083] A method for preparing a thick bearing coating based on a radio frequency magnetron sputtering process specifically comprises the following steps:
[0084] (1) Bearing pretreatment: The surface of the bearing substrate was treated with an ammonium persulfate solution with a mass concentration of 14% for 22 minutes at a temperature of 54°C. It was then placed in an aminosulfonic acid electrolyte with a mass concentration of 14% for anodization for 34 minutes at a temperature of 64°C. The treated bearing substrate was cleaned by ultrasonic oscillation.
[0085] (2) Preparation of aluminum-tin-copper alloy melt: The vacuum degree of the reaction chamber is 0.6×10 -6Pa environment, aluminum, tin and copper metal raw materials are added according to their mass fractions for smelting, the smelting temperature is controlled at 800°C, the smelting time is 0.8h, and aluminum-rich aluminum-tin-copper alloy melt and tin-rich aluminum-tin-copper alloy melt are respectively obtained; wherein, the composition of the aluminum-rich aluminum-tin-copper alloy melt is Sn: 23%, Cu: 0.4%, and the balance is Al; the composition of the tin-rich aluminum-tin-copper alloy melt is Al: 36%, Cu: 0.4%, and the balance is Sn.
[0086] (3) Preparation of composite aluminum-tin-copper alloy target:
[0087] The pressure casting method is adopted. The pre-melted aluminum-rich aluminum-tin-copper alloy melt is kept at 710℃. The pressure casting device is turned on and started with an initial casting pressure of 0.9MPa. The melt is slowly flowed through the casting pipe to the mold inlet at the copper matrix. The injection speed of the melt is controlled. The initial injection speed is 0.0002m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00006m 3 / s, allowing the melt to continue to slowly fill to the target thickness, forming an aluminum-rich alloy layer with a thickness of 2μm on the target copper substrate.
[0088] After the aluminum-rich alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt of this layer is completely solidified and tightly combined with the lower alloy layer, the pre-melted tin-rich aluminum-tin-copper alloy melt is maintained at 680°C, and the pressure casting device is turned on with an initial casting pressure of 0.9MPa to allow the melt to slowly flow through the casting pipe to the mold inlet. The injection speed of the melt is controlled, and the initial injection speed is 0.0002m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00006m 3 / s, allowing the melt to continue to slowly fill to the target thickness, forming a tin-rich alloy layer with a thickness of 2μm.
[0089] After the tin-rich alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt layer is completely solidified and tightly combined with the lower alloy layer, the casting operation is performed alternately until the target thickness of 28μm is reached. The top layer of the target material is a tin-rich alloy layer, and a composite aluminum-tin-copper alloy target material with a multi-layer alternating structure is obtained.
[0090] (4) PVD magnetron sputtering:
[0091] The bearing base, molybdenum target and composite aluminum-tin-copper alloy target were placed in the sputtering chamber respectively, and the chamber was evacuated to a vacuum degree of 0.6×10 -4Pa, slowly introduce argon to adjust the sputtering pressure to 0.6Pa; turn on the RF AC power supply, start the 45# steel target baffle, isolate the target and the bearing substrate from each other, use argon as the sputtering gas, control the RF frequency to ionize the argon, and use the ionized argon ions to bombard the bearing substrate. The RF frequency is 14MHz, the power is 800W, and the duration is 7min to improve the cleanliness of the microstructure of the bearing substrate.
[0092] The treated bearing substrate was preheated to 120°C, the target baffle was retracted, the distance between the molybdenum target and the bearing substrate was controlled to be 36mm, and the sputtering process parameters were controlled for sputtering: RF frequency 11MHz, power 580W, substrate bias -60V, sputtering gas pressure 6Pa, sputtering time 0.7h, and a molybdenum interlayer was obtained on the bearing substrate; during the sputtering process, the temperature on the back of the target was kept below 150°C.
[0093] The target baffle is started again, and the molybdenum interlayer is bombarded with ionized argon ions to activate its surface. The sputtering process parameters are: RF frequency of 10MHz, power of 550W, and duration of 3min. The target baffle is retracted again, and the composite aluminum-tin-copper alloy target is bombarded with ionized argon particles to deposit tin-rich coatings and aluminum-rich coatings with alternating compositions on the molybdenum interlayer of the bearing base. The sputtering process parameters are: RF frequency of 10MHz, power of 700W, substrate bias of -50V, sputtering pressure of 7Pa, and sputtering time of 14h; during the sputtering process, the temperature on the back of the target is kept below 100℃. First, a tin-rich aluminum-tin-copper alloy deposition is obtained on the molybdenum interlayer, and then an aluminum-rich aluminum-tin-copper alloy deposition is obtained. Subsequently, deposition is performed in sequence until all the targets are sputtered, and a bearing coating with an outermost coating of aluminum-rich aluminum-tin-copper alloy and a thickness of 28μm is obtained.
[0094] The bearing bush coating prepared in this embodiment has a smooth surface, uniform cross-sectional morphology, low porosity and high density. The adhesion of the bearing bush coating is tested by a cross-cut test, and the coating peeling is less than 5%, reaching the 4B grade. The coating has high bonding strength and is firmly bonded to the bearing bush substrate. After a 180° bending test, the coating has no peeling.
[0095] Example 5
[0096] A method for preparing a thick bearing coating based on a radio frequency magnetron sputtering process specifically comprises the following steps:
[0097] (1) Bearing pretreatment: The surface of the bearing substrate was treated with an ammonium persulfate solution with a mass concentration of 18% for 18 minutes at a temperature of 50°C; it was then placed in an aminosulfonic acid electrolyte with a mass concentration of 18% for anodization for 30 minutes at a temperature of 60°C, and the treated bearing substrate was obtained by ultrasonic oscillation cleaning.
[0098] (2) Preparation of aluminum-tin-copper alloy melt: The vacuum degree of the reaction chamber is 0.5×10 -6 Pa environment, aluminum, tin and copper metal raw materials are added according to their mass fractions for smelting, the smelting temperature is controlled at 830°C, the smelting time is 0.8h, and aluminum-rich aluminum-tin-copper alloy melt and tin-rich aluminum-tin-copper alloy melt are respectively obtained; wherein, the composition of the aluminum-rich aluminum-tin-copper alloy melt is Sn: 24%, Cu: 0.4%, and the balance is Al; the composition of the tin-rich aluminum-tin-copper alloy melt is Al: 37%, Cu: 0.4%, and the balance is Sn.
[0099] (3) Preparation of composite aluminum-tin-copper alloy target:
[0100] The pressure casting method is adopted. The pre-melted aluminum-rich aluminum-tin-copper alloy melt is kept at 720℃. The pressure casting device is turned on and started with an initial casting pressure of 0.8MPa. The melt is slowly flowed through the casting pipe to the mold inlet at the copper matrix. The injection speed of the melt is controlled. The initial injection speed is 0.0002m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00007m 3 / s, allowing the melt to continue to slowly fill to the target thickness, forming an aluminum-rich alloy layer with a thickness of 3μm on the target copper substrate.
[0101] After the aluminum-rich alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt of this layer is completely solidified and tightly combined with the lower alloy layer, the pre-melted tin-rich aluminum-tin-copper alloy melt is maintained at 690°C, and the pressure casting device is turned on with an initial casting pressure of 0.8MPa to allow the melt to slowly flow through the casting pipe to the mold inlet. The injection speed of the melt is controlled, and the initial injection speed is 0.0002m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00007m 3 / s, allowing the melt to continue to slowly fill to the target thickness, forming a tin-rich alloy layer with a thickness of 3μm.
[0102] After the tin-rich alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt layer is completely solidified and tightly combined with the lower alloy layer, the casting operation is performed alternately until the target thickness of 24μm is reached. The top layer of the target material is a tin-rich alloy layer, and a composite aluminum-tin-copper alloy target material with a multi-layer alternating structure is obtained.
[0103] (4) PVD magnetron sputtering:
[0104] The bearing base, molybdenum target and composite aluminum-tin-copper alloy target were placed in the sputtering chamber respectively, and the chamber was evacuated to a vacuum degree of 0.5×10 -4 Pa, slowly introduce argon to adjust the sputtering pressure to 0.6Pa; turn on the RF AC power supply, start the 45# steel target baffle, isolate the target and the bearing substrate from each other, use argon as the sputtering gas, control the RF frequency to ionize the argon, and use the ionized argon ions to bombard the bearing substrate. The RF frequency is 14MHz, the power is 800W, and the duration is 7min to improve the cleanliness of the microstructure of the bearing substrate.
[0105] The treated bearing substrate was preheated to 130°C, the target baffle was retracted, the distance between the molybdenum target and the bearing substrate was controlled to be 36mm, and the sputtering process parameters were controlled for sputtering: RF frequency 10MHz, power 620W, substrate bias -65V, sputtering gas pressure 7Pa, sputtering time 0.8h, and a molybdenum interlayer was obtained on the bearing substrate; during the sputtering process, the temperature on the back of the target was kept below 150°C.
[0106] The target baffle is started again, and the molybdenum interlayer is bombarded with ionized argon ions to activate its surface. The sputtering process parameters are: RF frequency of 10MHz, power of 600W, and duration of 4min. The target baffle is retracted again, and the composite aluminum-tin-copper alloy target is bombarded with ionized argon particles to deposit tin-rich coatings and aluminum-rich coatings with alternating compositions on the molybdenum interlayer of the bearing base. The sputtering process parameters are: RF frequency of 11MHz, power of 720W, substrate bias of -55V, sputtering pressure of 9Pa, and sputtering time of 12h; during the sputtering process, the temperature on the back of the target is kept below 100℃. First, a tin-rich aluminum-tin-copper alloy deposition is obtained on the molybdenum interlayer, and then an aluminum-rich aluminum-tin-copper alloy deposition is obtained. Then, deposition is carried out in sequence until all the targets are sputtered, and a bearing coating with an outermost coating of aluminum-rich aluminum-tin-copper alloy and a thickness of 24μm is obtained.
[0107] The bearing bush coating prepared in this embodiment has a smooth surface, uniform cross-sectional morphology, low porosity and high density. The adhesion of the bearing bush coating is tested by a cross-cut test, and the coating peeling is less than 5%, reaching the 4B grade. The coating has high bonding strength and is firmly bonded to the bearing bush substrate. After a 180° bending test, the coating has no peeling.
[0108] Example 6
[0109] A method for preparing a thick bearing coating based on a radio frequency magnetron sputtering process specifically comprises the following steps:
[0110] (1) Bearing pretreatment: The surface of the bearing substrate was treated with an ammonium persulfate solution with a mass concentration of 22% for 14 min at a temperature of 46°C. It was then placed in an aminosulfonic acid electrolyte with a mass concentration of 22% for anodization for 26 min at a temperature of 56°C. The treated bearing substrate was cleaned by ultrasonic oscillation.
[0111] (2) Preparation of aluminum-tin-copper alloy melt: The vacuum degree of the reaction chamber is 0.4×10 -6 Pa environment, aluminum, tin and copper metal raw materials are added according to their mass fractions for smelting, the smelting temperature is controlled at 860°C, the smelting time is 0.7h, and aluminum-rich aluminum-tin-copper alloy melt and tin-rich aluminum-tin-copper alloy melt are respectively obtained; wherein, the composition of the aluminum-rich aluminum-tin-copper alloy melt is Sn: 24%, Cu: 0.5%, and the balance is Al; the composition of the tin-rich aluminum-tin-copper alloy melt is Al: 37%, Cu: 0.5%, and the balance is Sn.
[0112] (3) Preparation of composite aluminum-tin-copper alloy target:
[0113] The pressure casting method is adopted. The pre-melted aluminum-rich aluminum-tin-copper alloy melt is kept at 730°C. The pressure casting device is turned on and started with an initial casting pressure of 0.7MPa. The melt is slowly flowed through the casting pipe to the mold inlet at the copper matrix. The injection speed of the melt is controlled. The initial injection speed is 0.0003m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00007m 3 / s, allowing the melt to continue to slowly fill to the target thickness, forming an aluminum-rich alloy layer with a thickness of 3μm on the target copper substrate.
[0114] After the aluminum-rich alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt of this layer is completely solidified and tightly combined with the lower alloy layer, the pre-melted tin-rich aluminum-tin-copper alloy melt is maintained at 700°C, and the pressure casting device is turned on with an initial casting pressure of 0.7MPa to allow the melt to slowly flow through the casting pipe to the mold inlet. The injection speed of the melt is controlled, and the initial injection speed is 0.0003m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00007m 3 / s, allowing the melt to continue to slowly fill to the target thickness, forming a tin-rich alloy layer with a thickness of 3μm.
[0115] After the tin-rich alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt layer is completely solidified and tightly combined with the lower alloy layer, the casting operation is performed alternately until the target thickness of 24μm is reached. The top layer of the target material is a tin-rich alloy layer, and a composite aluminum-tin-copper alloy target material with a multi-layer alternating structure is obtained.
[0116] (4) PVD magnetron sputtering:
[0117] The bearing base, molybdenum target and composite aluminum-tin-copper alloy target were placed in the sputtering chamber respectively, and the chamber was evacuated to a vacuum degree of 0.4×10 -4 Pa, slowly introduce argon to adjust the sputtering pressure to 0.8Pa; turn on the RF AC power supply, start the 45# steel target baffle, isolate the target and the bearing substrate from each other, use argon as the sputtering gas, control the RF frequency to ionize the argon, and use the ionized argon ions to bombard the bearing substrate. The RF frequency is 15MHz, the power is 850W, and the duration is 8min to improve the cleanliness of the microstructure of the bearing substrate.
[0118] The treated bearing substrate was preheated to 140°C, the target baffle was retracted, the distance between the molybdenum target and the bearing substrate was controlled to be 40mm, and the sputtering process parameters were controlled for sputtering: RF frequency 12MHz, power 650W, substrate bias -65V, sputtering gas pressure 8Pa, sputtering time 0.9h, and a molybdenum interlayer was obtained on the bearing substrate; during the sputtering process, the temperature on the back of the target was kept below 150°C.
[0119] The target baffle is started again, and the molybdenum interlayer is bombarded with ionized argon ions to activate its surface. The sputtering process parameters are: RF frequency of 11MHz, power of 650W, and duration of 5min. The target baffle is retracted again, and the composite aluminum-tin-copper alloy target is bombarded with ionized argon particles to deposit tin-rich coatings and aluminum-rich coatings with alternating compositions on the molybdenum interlayer of the bearing base. The sputtering process parameters are: RF frequency of 12MHz, power of 740W, substrate bias of -60V, sputtering pressure of 10Pa, and sputtering time of 12h; during the sputtering process, the temperature on the back of the target is kept below 100℃. First, a tin-rich aluminum-tin-copper alloy deposition is obtained on the molybdenum interlayer, and then an aluminum-rich aluminum-tin-copper alloy deposition is obtained. Subsequently, deposition is carried out in sequence until all the targets are sputtered, and a bearing coating with an outermost coating of aluminum-rich aluminum-tin-copper alloy and a thickness of 24μm is obtained.
[0120] The bearing bush coating prepared in this embodiment has a smooth surface, uniform cross-sectional morphology, low porosity and high density. The adhesion of the bearing bush coating is tested by a cross-cut test, and the coating peeling is less than 5%, reaching the 4B grade. The coating has high bonding strength and is firmly bonded to the bearing bush substrate. After a 180° bending test, the coating has no peeling.
[0121] Example 7
[0122] A method for preparing a thick bearing coating based on a radio frequency magnetron sputtering process specifically comprises the following steps:
[0123] (1) Bearing pretreatment: The surface of the bearing substrate was treated with an ammonium persulfate solution with a mass concentration of 26% for 12 min at a temperature of 42°C; it was then placed in an aminosulfonic acid electrolyte with a mass concentration of 26% for anodization for 22 min at a temperature of 52°C, and the treated bearing substrate was obtained by ultrasonic cleaning.
[0124] (2) Preparation of aluminum-tin-copper alloy melt: The vacuum degree of the reaction chamber is 0.3×10 -6 Pa environment, aluminum, tin and copper metal raw materials are added according to their mass fractions for smelting, the smelting temperature is controlled at 880°C, the smelting time is 0.6h, and aluminum-rich aluminum-tin-copper alloy melt and tin-rich aluminum-tin-copper alloy melt are respectively obtained; wherein, the composition of the aluminum-rich aluminum-tin-copper alloy melt is Sn: 25%, Cu: 0.5%, and the balance is Al; the composition of the tin-rich aluminum-tin-copper alloy melt is Al: 38%, Cu: 0.5%, and the balance is Sn.
[0125] (3) Preparation of composite aluminum-tin-copper alloy target:
[0126] The pressure casting method is adopted. The pre-melted aluminum-rich aluminum-tin-copper alloy melt is kept at 740℃. The pressure casting device is turned on and started with an initial casting pressure of 0.6MPa. The melt is slowly flowed through the casting pipe to the mold inlet at the copper matrix. The injection speed of the melt is controlled. The initial injection speed is 0.0003m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00008m 3 / s, allowing the melt to continue to slowly fill to the target thickness, forming an aluminum-rich alloy layer with a thickness of 4 μm on the target copper substrate.
[0127] After the aluminum-rich alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt of this layer is completely solidified and tightly combined with the lower alloy layer, the pre-melted tin-rich aluminum-tin-copper alloy melt is maintained at 710°C, and the pressure casting device is turned on with an initial casting pressure of 0.6MPa to allow the melt to slowly flow through the casting pipe to the mold inlet. The injection speed of the melt is controlled, and the initial injection speed is 0.0003m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00008m 3 / s, allowing the melt to continue to slowly fill to the target thickness, forming a tin-rich alloy layer with a thickness of 4μm.
[0128] After the tin-rich alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt layer is completely solidified and tightly combined with the lower alloy layer, the casting operation is performed alternately until the target thickness of 24μm is reached. The top layer of the target material is a tin-rich alloy layer, and a composite aluminum-tin-copper alloy target material with a multi-layer alternating structure is obtained.
[0129] (4) PVD magnetron sputtering:
[0130] The bearing base, molybdenum target and composite aluminum-tin-copper alloy target were placed in the sputtering chamber respectively, and the chamber was evacuated to a vacuum degree of 0.3×10 -4 Pa, slowly introduce argon to adjust the sputtering pressure to 0.8Pa; turn on the RF AC power supply, start the 45# steel target baffle, isolate the target and the bearing substrate from each other, use argon as the sputtering gas, control the RF frequency to ionize the argon, and use the ionized argon ions to bombard the bearing substrate. The RF frequency is 15MHz, the power is 850W, and the duration is 9min to improve the cleanliness of the microstructure of the bearing substrate.
[0131] The treated bearing substrate was preheated to 140°C, the target baffle was retracted, the distance between the molybdenum target and the bearing substrate was controlled to be 44mm, and the sputtering process parameters were controlled for sputtering: RF frequency 12MHz, power 680W, substrate bias -70V, sputtering gas pressure 9Pa, sputtering time 1h, and a molybdenum interlayer was obtained on the bearing substrate; during the sputtering process, the temperature on the back of the target was kept below 150°C.
[0132] The target baffle is started again, and the molybdenum interlayer is bombarded with ionized argon ions to activate its surface. The sputtering process parameters are: RF frequency of 12MHz, power of 650W, and duration of 5min. The target baffle is retracted again, and the composite aluminum-tin-copper alloy target is bombarded with ionized argon particles to deposit tin-rich coatings and aluminum-rich coatings with alternating compositions on the molybdenum interlayer of the bearing base. The sputtering process parameters are: RF frequency of 12MHz, power of 780W, substrate bias of -65V, sputtering pressure of 11Pa, and sputtering time of 12h; during the sputtering process, the temperature on the back of the target is kept below 100℃. First, a tin-rich aluminum-tin-copper alloy deposition is obtained on the molybdenum interlayer, and then an aluminum-rich aluminum-tin-copper alloy deposition is obtained. Subsequently, deposition is carried out in sequence until all the targets are sputtered, and a bearing coating with an outermost coating of aluminum-rich aluminum-tin-copper alloy and a thickness of 24μm is obtained.
[0133] The bearing bush coating prepared in this embodiment has a smooth surface, uniform cross-sectional morphology, low porosity and high density. The adhesion of the bearing bush coating is tested by a cross-cut test, and the coating peeling is less than 5%, reaching the 4B grade. The coating has high bonding strength and is firmly bonded to the bearing bush substrate. After a 180° bending test, the coating has no peeling.
[0134] Example 8
[0135] A method for preparing a thick bearing coating based on a radio frequency magnetron sputtering process specifically comprises the following steps:
[0136] (1) Bearing pretreatment: The surface of the bearing substrate was treated with a 30% ammonium persulfate solution for 10 min at 40°C. The substrate was then anodized in a 30% aminosulfonic acid electrolyte for 20 min at 50°C. The treated bearing substrate was cleaned by ultrasonic oscillation.
[0137] (2) Preparation of aluminum-tin-copper alloy melt: The vacuum degree of the reaction chamber is 0.2×10 -6 Pa environment, aluminum, tin and copper metal raw materials are added according to their mass fractions for smelting, the smelting temperature is controlled at 900°C, the smelting time is 0.5h, and aluminum-rich aluminum-tin-copper alloy melt and tin-rich aluminum-tin-copper alloy melt are respectively obtained; wherein, the composition of the aluminum-rich aluminum-tin-copper alloy melt is Sn: 25%, Cu: 0.5%, and the balance is Al; the composition of the tin-rich aluminum-tin-copper alloy melt is Al: 38%, Cu: 0.5%, and the balance is Sn.
[0138] (3) Preparation of composite aluminum-tin-copper alloy target:
[0139] The pressure casting method is adopted. The pre-melted aluminum-rich aluminum-tin-copper alloy melt is kept at 750℃. The pressure casting device is turned on and started with an initial casting pressure of 0.5MPa. The melt is slowly flowed through the casting pipe to the mold inlet at the copper matrix. The injection speed of the melt is controlled. The initial injection speed is 0.0003m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00008m 3 / s, allowing the melt to continue to slowly fill to the target thickness, forming an aluminum-rich alloy layer with a thickness of 4 μm on the target copper substrate.
[0140] After the aluminum-rich alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt of this layer is completely solidified and tightly combined with the lower alloy layer, the pre-melted tin-rich aluminum-tin-copper alloy melt is maintained at 720°C, and the pressure casting device is turned on with an initial casting pressure of 0.5MPa to allow the melt to slowly flow through the casting pipe to the mold inlet. The injection speed of the melt is controlled, and the initial injection speed is 0.0003m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00008m 3 / s, allowing the melt to continue to slowly fill to the target thickness, forming a tin-rich alloy layer with a thickness of 4μm.
[0141] After the tin-rich alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt layer is completely solidified and tightly combined with the lower alloy layer, the casting operation is performed alternately until the target thickness of 24μm is reached. The top layer of the target material is a tin-rich alloy layer, and a composite aluminum-tin-copper alloy target material with a multi-layer alternating structure is obtained.
[0142] (4) PVD magnetron sputtering:
[0143] The bearing base, molybdenum target and composite aluminum-tin-copper alloy target were placed in the sputtering chamber respectively, and the chamber was evacuated to a vacuum degree of 0.2×10 -4 Pa, slowly introduce argon to adjust the sputtering pressure to 0.8Pa; turn on the RF AC power supply, start the 45# steel target baffle, isolate the target and the bearing substrate from each other, use argon as the sputtering gas, control the RF frequency to ionize the argon, and use the ionized argon ions to bombard the bearing substrate. The RF frequency is 15MHz, the power is 900W, and the duration is 10min to improve the cleanliness of the microstructure of the bearing substrate.
[0144] The treated bearing substrate was preheated to 150°C, the target baffle was retracted, the distance between the molybdenum target and the bearing substrate was controlled to be 50mm, and the sputtering process parameters were controlled for sputtering: RF frequency 12MHz, power 700W, substrate bias -70V, sputtering gas pressure 9Pa, sputtering time 1h, and a molybdenum interlayer was obtained on the bearing substrate; during the sputtering process, the temperature on the back of the target was kept below 150°C.
[0145] The target baffle is started again, and the molybdenum interlayer is bombarded with ionized argon ions to activate its surface. The sputtering process parameters are: RF frequency of 12MHz, power of 700W, and duration of 5min. The target baffle is retracted again, and the composite aluminum-tin-copper alloy target is bombarded with ionized argon particles to deposit tin-rich coatings and aluminum-rich coatings with alternating compositions on the molybdenum interlayer of the bearing base. The sputtering process parameters are: RF frequency of 12MHz, power of 800W, substrate bias of -70V, sputtering pressure of 12Pa, and sputtering time of 12h; during the sputtering process, the temperature on the back of the target is kept below 100℃. First, a tin-rich aluminum-tin-copper alloy deposition is obtained on the molybdenum interlayer, and then an aluminum-rich aluminum-tin-copper alloy deposition is obtained. Subsequently, deposition is performed in sequence until all the targets are sputtered, and a bearing coating with an outermost coating of aluminum-rich aluminum-tin-copper alloy and a thickness of 24μm is obtained.
[0146] The bearing bush coating prepared in this embodiment has a smooth surface, uniform cross-sectional morphology, low porosity and high density. The adhesion of the bearing bush coating is tested by a cross-cut test, and the coating peeling is less than 5%, reaching the 4B grade. The coating has high bonding strength and is firmly bonded to the bearing bush substrate. After a 180° bending test, the coating has no peeling.
[0147] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a thick coating on a bearing bush based on a radio frequency magnetron sputtering process, characterized in that: The specific steps include: (1) Bearing pretreatment: Treat the surface of the bearing base to remove grease and impurities on the surface to obtain the treated bearing base; (2) preparing an aluminum-tin-copper alloy melt: adding metal raw materials for smelting under a vacuum environment to obtain an aluminum-rich aluminum-tin-copper alloy melt and a tin-rich aluminum-tin-copper alloy melt; (3) Preparation of composite aluminum-tin-copper alloy target: Alternately casting an aluminum-rich aluminum-tin-copper alloy melt and a tin-rich aluminum-tin-copper alloy melt to obtain a composite aluminum-tin-copper alloy target material with a multi-layer alternating structure, wherein the top layer of the target material is a tin-rich alloy layer; (4) PVD magnetron sputtering: The bearing substrate obtained in step (1) is sputtered and cleaned by using a radio frequency alternating current power supply. After the cleaned bearing substrate is preheated, it is sputtered by a molybdenum target to obtain a molybdenum interlayer; the molybdenum interlayer is surface activated, and then it is sputtered by a composite aluminum-tin-copper alloy target to alternately deposit tin-rich coatings and aluminum-rich coatings on the molybdenum interlayer to obtain a magnetron sputtering bearing thick coating.
2. The method for preparing a thick coating on a bearing bush based on a radio frequency magnetron sputtering process according to claim 1, characterized in that: In the step (1), the surface of the bearing base is treated by: treating the surface of the bearing base with an ammonium persulfate solution, placing the bearing base in an aminosulfonic acid electrolyte for anodizing, and then cleaning the bearing base with ultrasonic oscillation to obtain the treated bearing base; The mass concentration of the ammonium persulfate solution is 10% to 30%, the surface treatment time is 10min to 30min, and the temperature is 40°C to 60°C; the mass concentration of the aminosulfonic acid electrolyte is 10% to 30%, the oxidation time is 20min to 40min, and the temperature is 50°C to 70°C.
3. The method for preparing a thick coating on a bearing bush based on a radio frequency magnetron sputtering process according to claim 1, characterized in that: In the step (2), the vacuum degree of the environment is ≥ 1×10 -6 Pa; the raw materials used to prepare the aluminum-rich aluminum-tin-copper alloy are calculated by mass fraction as follows: Sn: 22%-25%, Cu: 0.3%-0.5%, and the balance is Al; the raw materials used to prepare the tin-rich aluminum-tin-copper alloy are calculated by mass fraction as follows: Al: 35%-38%, Cu: 0.3%-0.5%, and the balance is Sn; the vacuum melting temperature is controlled at 750°C-900°C, and the melting time is 0.5h-1h.
4. The method for preparing a thick coating on a bearing bush based on a radio frequency magnetron sputtering process according to claim 1, characterized in that: In the step (3), the preparation process of the composite aluminum-tin-copper alloy target is specifically as follows: by pressure casting, an aluminum-rich aluminum-tin-copper alloy melt is injected into a mold to form an aluminum-rich alloy layer on the target copper substrate, and then a tin-rich aluminum-tin-copper alloy melt is covered on the aluminum-rich alloy layer in the same manner to form a tin-rich alloy layer, and the casting operation is performed alternately to obtain a composite aluminum-tin-copper alloy target with a multi-layer alternating structure; The specific injection method of the aluminum-rich aluminum-tin-copper alloy melt is as follows: the pre-smelted aluminum-rich aluminum-tin-copper alloy melt is maintained at 650° C. to 750° C., a pressure casting device is started with an initial casting pressure of 0.5 MPa to 1.0 MPa, and the melt is slowly flowed through the casting pipe to the mold inlet at the copper substrate, and the injection speed of the melt is controlled, and the initial injection speed is 0.0001 m / s. 3 / s~0.0003m 3 / s, when the thickness is close to the target thickness, gradually reduce the casting pressure to near zero, and fine-tune the injection speed to 0.00005m 3 / s~0.00008m 3 / s, allowing the melt to continue to slowly fill to the target thickness to form an aluminum-rich alloy layer.
5. The method for preparing a thick coating on a bearing bush based on a radio frequency magnetron sputtering process according to claim 4, characterized in that: The target thickness of each aluminum-rich alloy layer and tin-rich alloy layer is 2μm to 4μm, and the thickness of the composite aluminum-tin-copper alloy target is 20μm to 28μm. After each alloy layer is cast, the temperature control system at the bottom of the mold is adjusted to gradually solidify the alloy layer. After the melt of this layer is completely solidified and tightly combined with the lower alloy layer, the next step is carried out.
6. The method for preparing a thick coating on a bearing bush based on a radio frequency magnetron sputtering process according to claim 1, characterized in that: In the step (4), the process of sputtering and cleaning the bearing substrate is specifically as follows: placing the bearing substrate, the molybdenum target material, and the composite aluminum-tin-copper alloy target material in a sputtering chamber respectively, evacuating the chamber to a vacuum, and slowly introducing argon gas to adjust the pressure; turning on the radio frequency AC power supply, starting the self-made target baffle, isolating the target material and the bearing substrate from each other, using argon gas as the sputtering gas, controlling the radio frequency frequency to ionize the argon gas, and using the ionized argon gas ions to bombard the bearing substrate to improve the cleanliness of the microstructure of the bearing substrate; The sample chamber is evacuated to a vacuum degree of ≥1×10 -4 Pa, introduce argon gas to adjust the sputtering pressure to 0.6Pa~0.8Pa; The parameters of the sputtering bearing bush substrate are: radio frequency of 13 MHz to 15 MHz, power of 700 W to 900 W, and duration of 5 min to 10 min.
7. The method for preparing a thick coating on a bearing bush based on a radio frequency magnetron sputtering process according to claim 1, characterized in that: In the step (4), when sputtering and cleaning the bearing shell substrate, the target baffle is started, argon gas is used as the sputtering gas, and the RF frequency is controlled to ionize the argon gas, the RF frequency is 13 MHz to 15 MHz, the power is 700 W to 900 W, and the duration is 5 min to 10 min; After the bearing base is preheated, the target baffle is retracted, and the distance between the target and the bearing base is controlled to sputter the molybdenum interlayer; the preheating temperature of the bearing base is 100°C to 150°C, and the distance between the target and the bearing base is 30mm to 50mm.
8. The method for preparing a thick bearing coating based on a radio frequency magnetron sputtering process according to claim 1 is characterized in that: In the step (4), the process parameters of the molybdenum target sputtering the bearing base are specifically as follows: the radio frequency is 10MHz to 12MHz, the power is 500W to 700W, the substrate bias is -50V to -70V, the sputtering gas pressure is 6Pa to 9Pa, and the sputtering time is 0.5h to 1h; during the sputtering process, the temperature of the back of the target is kept below 150°C; The surface activation process of the bearing bush molybdenum interlayer is specifically as follows: starting the target baffle, bombarding the molybdenum interlayer with ionized argon ions, with a radio frequency of 10MHz to 12MHz, a power of 500W to 700W, and a duration of 3min to 5min.
9. The method for preparing a thick coating on a bearing bush based on a radio frequency magnetron sputtering process according to claim 1, characterized in that: In the step (4), the process of sputtering the composite aluminum-tin-copper alloy target is specifically as follows: retracting the target baffle, bombarding the composite aluminum-tin-copper alloy target with ionized argon gas particles, and depositing a tin-rich coating and an aluminum-rich coating with alternating compositions on the molybdenum interlayer of the bearing base, first obtaining a tin-rich aluminum-tin-copper alloy deposition, then obtaining an aluminum-rich aluminum-tin-copper alloy deposition, and then depositing in sequence until all the target materials are sputtered, thereby obtaining a bearing coating whose outermost coating is an aluminum-rich aluminum-tin-copper alloy; The process parameters of the sputtering composite aluminum-tin-copper alloy target are: RF frequency of 10MHz to 12MHz, power of 600W to 800W, substrate bias of -50V to -70V, sputtering gas pressure of 6Pa to 9Pa, and sputtering time of 10h to 14h; during the sputtering process, the temperature on the back of the target is kept below 100°C; the thickness of the obtained bearing coating is 20μm to 28μm.
10. The method for preparing a thick coating on a bearing bush based on a radio frequency magnetron sputtering process according to claim 1, characterized in that: In the step (4), the adhesion of the thick coating of the magnetron sputtering bearing bush is tested by the cross-grid method, and the coating bonding strength reaches 4B level or above; after the 180° bending test, the coating does not peel off.
Citation Information
Patent Citations
Treatment method for improving coating bonding strength of bearing bush
CN106319476A
Bearing bush composite coating processing method and bearing bush composite coating based on PVD technology
CN112111717A